The role of a non-governmental organization in the improvement of employment in Finland : a case study of Jyväskylän Katulähetys ry in the city of Jyväskylä - Sama, Thomas Babila (2007)
The purpose of this thesis was to discuss whether an NGO is a potential alternative institution for the improvement of employment in Finland. The study was designed to get an overview of the roles played by NGOs in improving employment in Finland. It was aimed at reviewing the existing relation between the Government and NGOs, and also to assess the case study NGO with regards to the improvement of employment in the city of Jyväskylä. This study is descriptive and Jyväskylän Katulähetys ry, an NGO based in Jyväskylä was chosen as the case study NGO. The empirical data was collected through questionnaires, interviews and participant observation with the involvement of sixteen employees and an official of the case study NGO. The study revealed that NGOs in Finland play complementary roles in their cooperation partnership with the government. In this regard, the case study NGO was found to be playing a vital role in improving employment in the city of Jyväskylä, but the skill development training provided by the NGO to its employees, was found to be inadequate for their employability in the open labour market. The study concluded that, for the case study NGO to become a potential alternative institution for the improvement of employment in the city of Jyväskylä, it must improve the skill development training of its employees among other things. NGOs and the Third Sector are used interchangeably in this study.